Socialization Of The Implementation Of The K3 Management System In Schools - Kemas Muhammad Ade Isnaeni; Dwi Hanadya; Nyayu Ully Auliana (Cita konsultindo, 2024)
One of the characteristics of construction projects is that they have a high risk of accidents. With the increasing use of sophisticated work tools, even though they have been equipped with safety systems, the risk of accidents is still getting bigger. Now, accidents are considered the result of incorrect organizational and management factors. Then the role of management is very meaningful in accident prevention. Community Service activities at SD IT Robbani Indralaya were carried out smoothly and ran according to the schedule that had been set. During the activity, participants enthusiastically followed the exposure displayed about school K3, the potential dangers that exist in schools, and efforts to control them. The results achieved from community service activities at SD IT Robbani Indralaya are: Increased knowledge about the basic concepts of school K3, Increased awareness of potential dangers from activities carried out at school. Understand efforts to control potential hazards that exist in the school environment. In conclusion, this paper discusses, the role of Occupational Safety and Health management system (OHSMS) is discussed from the function of the management function, the resources used, and other relevant aspects.